Lire à contre-courant les textes de Jean Lorrain - Ferrety Montiel, Victoria (Verbum – Analecta Neolatina, 2025)
For Lorrain, storytelling was as important as life itself. He was feared and hated for his writing and personality, and was an endless source of inspiration for the malicious gossip and attacks of his detractors, whom he portrayed in his famous Pall Mall Semaine without their knowledge.